Providing information about triclabendazole resistance status influences farmers to change liver fluke control practices. (27th July 2020) - Coyne, Lucy Alice; Bellet, Camille; Latham, Sophia M; Williams, Diana
Abstract : Background: Reports of disease and production losses associated with Fasciola hepatica, the common liver fluke, have increased in recent years. Resistance to triclabendazole, one of the principal veterinary medicines used to prevent losses, has been reported and is now considered widespread in fluke endemic regions of the UK. Methods: Thirteen farmers participated in a trial in 2013 and the triclabendazole resistance status was obtained for each farm. Based on these results, a knowledge exchange programme on fluke control was delivered to nearly 100 farmers in the region. In this follow-up study, 11 farmers involved in the original trial, participated in semistructured in-depth qualitative interviews in July 2017. Results: Overall, participants identified benefits from participating in the 2013 trial, gaining information about triclabendazole resistance on their farms and knowledge about fluke control. The information on their farm's resistance status was a driver for changing their liver fluke control programmes. Factors such as habitual and repetitive behaviours, grazing restrictions due to agri-environmental schemes, economic pressures and climate change were identified that could impede or prevent the adoption of new control strategies. Conclusions: The study highlights the significance of resistance to triclabendazole and the impact of knowledge exchange programmes in changing liver fluke control practices.